FEMALE ENTREPRENEURSHIP AS A CHOICE TO GO OUT OF THE POVERTY - Zh. A. Temirbekova (Academic Journal of Physical and Chemical Sciences, 2019)
Women decide to start a business for a variety of reasons. Extant research shows that if some women decide to establish their own enterprises in order to go out of the poverty by earning some income, others decide to be involved in a business world with an aim of being their own-boss and independent. Thus, the aim of this research is to explore the main reasons of women’s business establishment decisions. Based on an in-depth study of an earlystage female entrepreneur owning a small-sized enterprise, this study finds out that women start a business with an aim of earning some income in order to feed their children and providing them with better living conditions. Thus, entrepreneurship for women was a way to go out of the poverty. Once the business passed over the start-up stage, it allowed owners to have some savings in addition to the profit, through which they were covering their living expenses.